Ethnic pluralism, immigration and entrepreneurship. Issue 1 (2nd January 2019) - Mickiewicz, Tomasz; Hart, Mark; Nyakudya, Frederick; Theodorakopoulos, Nicholas
ABSTRACT: This paper considers the effects of immigration and ethnicity on entrepreneurship, distinguishing between the individual traits and the environmental characteristics. It looks beyond the resource-opportunity framework and occupational choice: culture and values matter. Yet, instead of assigning the latter to specific ethnic features, they are related here to both immigration and to the social environment defined by the share of immigrants, and by ethnic diversity. Empirical evidence provided in this paper is based on Global Entrepreneurship Monitor (GEM) UK data, 2003–13. Having more immigrants in the locality enhances entrepreneurship. With an increase in ethnic diversity the likelihood of being engaged in start-up activity decreases then increases.